Alkaline Earth Metal Aluminates as Catalysts for Imine Hydrogenation - Elsen, Holger; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Organometallics, 2020)
Alkaline earth (Ae) metal complexes with the alanate anion AlH4 - have been prepared by salt metathesis between NaAlH4 and AeCl2 in THF and could be isolated as Mg(AlH4)2·(THF)4, Ca(AlH4)2·(THF)4, and Sr(AlH4)2·(THF)5. The previously reported crystal structure of the Mg alanate complex shows bonding of AlH4 - with one bridging hydride, H3Al-(μ-H)-Mg, while the Ca and Sr alanates show a combination of H3Al-(μ-H)-Ae and H2Al-(μ-H)2-Ae bridging. The heteroleptic β-diketiminate complexes (DIPPBDI)Mg(AlH4)·THF and (DIPPBDI)Ca(AlH4)·(THF)2 have been prepared by reaction of the corresponding Ae hydride complexes with AlH3·(THF)2 [DIPPBDI = DIPP-NC(Me)C(H)C(Me)N-DIPP, where DIPP = 2,6-diisopropylphenyl]. Crystal structures show H2Al-(μ-H)2-Ae bridging. The Ca complex decomposes at room temperature by reduction of the β-diketiminate anion. Density functional theory calculations (B3PW91/def2tzvpp) show that the formation of Ae(AlH4)2 from AeH2 and AlH3 is exothermic by ΔH (kilocalories per mole): Be, -68.8; Mg, -66.1; Ca, -95.4; Sr, -100.9; Ba, -112.3. Calculations of NPA charges on LiAlH4 and the Ae alanate complexes (Ae = Mg, Ca, or Sr) show that these are highly ionic salts in which the charge on AlH4 - of approximately -0.95 is hardly dependent on the countercation. Compared to LiAlH4, the Ae alanates are very efficient catalysts for imine hydrogenation, clearly extending the substrate scope. In addition to aldimines RC(H)═NR′ (R/R′ = Ph/tBu, tBu/tBu, nPr/tBu, or Ph/Ph), ketimine PhC(Me)═NtBu could be reduced. The salt [Bu4N+][AlH4 -] is catalytically not active, which shows that the s-block metal is crucial. The highest activities were found for the heterobimetallic Ca and Sr alanates.
CRIS-Team Scopus Importer:2020-06-09

Application of a Stable and Soluble Dibenzylbarium Reagent in the Synthesis of a Barium Imido Cluster - Rösch, Bastian; Martin, Johannes; Eyselein, Jonathan; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Organometallics, 2021)
The complex (DMAT)2Ba·(THF)2 (DMAT = 2-dimethylamino-α-trimethylsilylbenzyl) was prepared by a salt metathesis reaction between (DMAT)K and BaI2 in THF, and crystals were isolated in 83% yield. This monomeric complex dissolves well in aromatic or ethereal solvents and is also stable at higher temperatures in solution. Structural details and NMR parameters reveal a high degree of charge delocalization in the DMAT aryl ring. Comparison with identical Ca and Sr complexes, (DMAT)2Ae·(THF)2 (Ae = Ca and Sr), shows that the extent of delocalization increases down group 2: Ca < Sr < Ba. Due to chirality at the benzylic carbon, in solution the heterochiral R,S-isomer and homochiral R,R/S,S-isomers exist in equilibrium. A temperature-dependent NMR study gives an estimate of the Ae-C and Ae-N bond energies which decrease down the group: Ca > Sr > Ba. Although the DMAT carbanion is stabilized by resonance and negative hyperconjugation, (DMAT)2Ba·(THF)2 is still a very potent deprotonation reagent. Double deprotonation of Ph3SiNH2 gave the first Ba imido complex. A similar reaction using (DMAT)2Sr·(THF)2 gave the analogue Sr imido complex. Comparison with reported structures shows trends for the full series [(Ph3SiN)Ae·(THF)]4 (Ae = Mg, Ca, Sr, and Ba) which crystallize as tetramers with very stable, ionically bound heterocubane Ae4N4 cores.
CRIS-Team Scopus Importer:2021-06-04

Carbon-Halogen Bond Activation with Powerful Heavy Alkaline Earth Metal Hydrides - Wiesinger, Michael; Rösch, Bastian; Knüpfer, Christian; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2021)
Reaction of [(DIPePBDI)SrH]2 with C6H5X (X=Cl, Br, I) led to hydride-halogenide exchange (DIPePBDI=HC[(Me)CN-2,6-(3-pentyl)phenyl]2). Conversion rates increase with increasing halogen size (F<Cl<Br<I). Reaction of [(DIPePBDI)SrH]2 with C6H5F was slow and ill-defined but addition of C6H4F2 gave smooth hydride-fluoride exchange. After addition of THF the full range of Sr halogenides was structurally characterized: [(DIPePBDI)SrX ⋅ THF]2 (X=F, Cl, Br, I). Mixtures of AeN“2 and PhSiH3 in situ formed less defined but more robust Ae metal hydride clusters (AexN”yHz, Ae=Ca, Sr, Ba and N“=N(SiMe3)2) which are able to hydrodefluorinate C6H5F. Conversion rates increase with increasing metal size (Ca<Sr<Ba). Also alkylfluorides (1-F-hexane, F-cyclohexane, 1-F-adamantane) could be converted but, due to solubility problems of the Ba species, the fastest conversion was found for Sr. These AeN”2/PhSiH3 mixtures also converted SF6 at room temperature to give undefined decomposition products. Addition of Me6Tren to a SrN“2/PhSiH3 led to crystallization of [Sr6N”2H9 ⋅ (Me6Tren)3+][SrN“3−]; Me6Tren=tris[2-(dimethylamino)ethyl]amine). After hydrodefluorination, Sr6N”4F8 ⋅ (Me6Tren)2 was formed and structurally characterized. Dissolution in THF led to cluster growth and the larger cluster Sr16N“8F24 ⋅ (THF)12 is structurally characterized. DFT calculations support that hydrodehalogenation of halobenzenes follows a concerted nucleophilic aromatic substitution mechanism (cSNAr).
CRIS-Team Scopus Importer:2021-08-27
Keywords: Alkaline-earth metal; DFT calculation; Hydride; Hydrodehalogenation

Cationic Aluminium Complexes as Catalysts for Imine Hydrogenation - Friedrich, Alexander; Eyselein, Jonathan; Elsen, Holger; Langer, Jens; Pahl, Jürgen; Wiesinger, Michael; Harder, Sjoerd (Chemistry - A European Journal, 2021)
Strongly Lewis acidic cationic aluminium complexes, stabilized by β–diketiminate (BDI) ligands and free of Lewis bases, have been prepared as their B(C6F5)4− salts and were investigated for catalytic activity in imine hydrogenation. The backbone (R1) and N (R2) substituents on the R1,R2BDI ligand (R1,R2BDI=HC[C(R1)N(R2)]2) influence sterics and Lewis acidity. Ligand bulk increases along the row Me,DIPPBDI<Me,DIPePBDI≈tBu,DIPPBDI<tBu,DIPePBDI; DIPP=2,6-C(H)Me2-phenyl, DIPeP=2,6-C(H)Et2-phenyl. The Gutmann-Beckett test showed acceptor numbers of: (tBu,DIPPBDI)AlMe+ 85.6, (tBu,DIPePBDI)AlMe+ 85.9, (Me,DIPPBDI)AlMe+ 89.7, (Me,DIPePBDI)AlMe+ 90.8, (Me,DIPPBDI)AlH+ 95.3. Steric and electronic factors need to be balanced for catalytic activity in imine hydrogenation. Open, highly Lewis acidic, cations strongly coordinate imine rendering it inactive as a Frustrated Lewis Pair (FLP). The bulkiest cations do not coordinate imine but its combination is also not an active catalyst. The cation (tBu,DIPPBDI)AlMe+ shows the best catalytic activity for various imines and is also an active catalyst for the Tishchenko reaction of benzaldehyde to benzylbenzoate. DFT calculations on the mechanism of imine hydrogenation catalysed by cationic Al complexes reveal two interconnected catalytic cycles operating in concert. Hydrogen is activated either by FLP reactivity of an Al⋅⋅⋅imine couple or, after formation of significant quantities of amine, by reaction with an Al⋅⋅⋅amine couple. The latter autocatalytic Al⋅⋅⋅amine cycle is energetically favoured.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Aluminium; cations; DFT; hydrogenation; imine

d–d Dative Bonding Between Iron and the Alkaline-Earth Metals Calcium, Strontium, and Barium - Stegner, Philipp; Färber, Christian; Oetzel, Jan; Siemeling, Ulrich; Wiesinger, Michael; Langer, Jens; Pan, Sudip; Holzmann, Nicole; Frenking, Gernot; Albold, Uta; Sarkar, Biprajit; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Double deprotonation of the diamine 1,1′-(tBuCH2NH)-ferrocene (1-H2) by alkaline-earth (Ae) or EuII metal reagents gave the complexes 1-Ae (Ae=Mg, Ca, Sr, Ba) and 1-Eu. 1-Mg crystallized as a monomer while the heavier complexes crystallized as dimers. The Fe⋅⋅⋅Mg distance in 1-Mg is too long for a bonding interaction, but short Fe⋅⋅⋅Ae distances in 1-Ca, 1-Sr, and 1-Ba clearly support intramolecular Fe⋅⋅⋅Ae bonding. Further evidence for interactions is provided by a tilting of the Cp rings and the related 1H NMR chemical-shift difference between the Cp α and β protons. While electrochemical studies are complicated by complex decomposition, UV/Vis spectral features of the complexes support Fe→Ae dative bonding. A comprehensive bonding analysis of all 1-Ae complexes shows that the heavier species 1-Ca, 1-Sr, and 1-Ba possess genuine Fe→Ae bonds which involve vacant d-orbitals of the alkaline-earth atoms and partially filled d-orbitals on Fe. In 1-Mg, a weak Fe→Mg donation into vacant p-orbitals of the Mg atom is observed.
CRIS-Team Scopus Importer:2020-07-10
Keywords: alkaline-earth metals; ferrocene; metal–metal bonding; theoretical chemistry

Dibenzotropylidene Substituted Ligands for Early Main Group Metal-Alkene Bonding - Martin, Johannes; Langer, Jens; Wiesinger, Michael; Elsen, Holger; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
New N-ligands with TROP-substituents are introduced (TROP = [5H]dibenzo[a,d]cyclohepten-5-yl): (TROP)(DIPP)N (DIPP = 2,6-diisopropylphenyl), TROPBDI (HC[C(Me)N-TROP]2) and the β-diketiminate ligand TROP–DIPPBDI with TROP and DIPP substituents at N. Several Li, Mg, Ca and Zn complexes with these ligands have been isolated and were characterized by X-ray diffraction. While TROP-substituents in the protonated ligands show endo-exo exchange, TROP-substituents in the metal complexes are in endo-conformation due to metal···alkene bonding. Short contacts between the metal and the TROP alkene unit are observed and some of these are the shortest reported; (TROPBDI)Li: Li···C 2.416(3) Å, [(TROP)(DIPP)N]2Ca: Ca···C 2.742(2) Å. TROPBDI shows superior metal shielding properties to the Li complex with a buried volume of VB = 78.7 %. DFT calculations on [(TROP)(DIPP)N]2Mg show a minimum with asymmetric Mg···alkene bonding. Symmetric Mg···alkene bonding is a transition state 1.9 kcal/mol higher in energy. Asymmetry in alkene-Mg bonding is explained by an ion-induced polarization of the C=C bond and electrostatic Mg2+···(δ-)C=C(δ+) attraction. The TROP-substituent stabilizes low valent radical species but attempts to isolate (TROPBDI)Mg· or (TROPBDI)Zn· by reduction of the iodide precursors failed. Intensely black coloured raw products hint towards formation of radical species. Several radical decomposition products have been structurally characterized.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Amides; Early main group metals; Metal-alkene bonding; Radicals; β-Diketiminate

Heterometallic Mg−Ba Hydride Clusters in Hydrogenation Catalysis - Wiesinger, Michael; Knüpfer, Christian; Elsen, Holger; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (ChemCatChem, 2021)
Reaction of a MgN“2/BaN”2 mixture (N“=N(SiMe3)2) with PhSiH3 gave three unique heterometallic Mg/Ba hydride clusters: Mg5Ba4H11N”7 ⋅ (benzene)2 (1), Mg4Ba7H13N“9 ⋅ (toluene)2 (2) and Mg7Ba12H26N”12 (3). Product formation is controlled by the Mg/Ba ratio and temperature. Crystal structures are described. While 3 is fully insoluble, clusters 1 and 2 retain their structures in aromatic solvents. DFT calculations and AIM analyses indicate highly ionic bonding with Mg−H and Ba−H bond paths. Also unusual H−⋅⋅⋅H− bond paths are observed. Catalytic hydrogenation with MgN“2, BaN”2 and the mixture MgN“2/BaN”2 has been studied. Whereas MgN“2 is only active in imine hydrogenation, alkene and alkyne hydrogenation needs the presence of Ba. The catalytic activity of the MgN”2/BaN“2 mixture lies in general between that of its individual components and strong cooperative effects are not evident.
CRIS-Team Scopus Importer:2021-09-17
Keywords: alkaline earth metal; catalysis; DFT calculations; heterometallic; hydride

Highly Active Superbulky Alkaline Earth Metal Amide Catalysts for Hydrogenation of Challenging Alkenes and Aromatic Rings - Martin, Johannes; Knüpfer, Christian; Eyselein, Jonathan; Färber, Christian; Grams, Samuel; Langer, Jens; Thum, Katharina; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Two series of bulky alkaline earth (Ae) metal amide complexes have been prepared: Ae[N(TRIP)2]2 (1-Ae) and Ae[N(TRIP)(DIPP)]2 (2-Ae) (Ae=Mg, Ca, Sr, Ba; TRIP=SiiPr3, DIPP=2,6-diisopropylphenyl). While monomeric 1-Ca was already known, the new complexes have been structurally characterized. Monomers 1-Ae are highly linear while the monomers 2-Ae are slightly bent. The bulkier amide complexes 1-Ae are by far the most active catalysts in alkene hydrogenation with activities increasing from Mg to Ba. Catalyst 1-Ba can reduce internal alkenes like cyclohexene or 3-hexene and highly challenging substrates like 1-Me-cyclohexene or tetraphenylethylene. It is also active in arene hydrogenation reducing anthracene and naphthalene (even when substituted with an alkyl) as well as biphenyl. Benzene could be reduced to cyclohexane but full conversion was not reached. The first step in catalytic hydrogenation is formation of an (amide)AeH species, which can form larger aggregates. Increasing the bulk of the amide ligand decreases aggregate size but it is unclear what the true catalyst(s) is (are). DFT calculations suggest that amide bulk also has a noticeable influence on the thermodynamics for formation of the (amide)AeH species. Complex 1-Ba is currently the most powerful Ae metal hydrogenation catalyst. Due to tremendously increased activities in comparison to those of previously reported catalysts, the substrate scope in hydrogenation catalysis could be extended to challenging multi-substituted unactivated alkenes and even to arenes among which benzene.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Alkaline Earth Metals; Alkenes; Aromatic rings; DFT calculations; Hydrogenation

Insights into LiAlH4 Catalyzed Imine Hydrogenation - Elsen, Holger; Langer, Jens; Ballmann, Gerd; Wiesinger, Michael; Harder, Sjoerd (Chemistry - A European Journal, 2020)
Commercial LiAlH4 can be used in catalytic quantities in the hydrogenation of imines to amines with H2. Combined experimental and theoretical investigations give deeper insight in the mechanism and identifies the most likely catalytic cycle. Activity is lost when Li in LiAlH4 is exchanged for Na or K. Exchanging Al for B or Ga also led to dramatically reduced activities. This indicates a heterobimetallic mechanism in which cooperation between Li and Al is crucial. Potential intermediates on the catalytic pathway have been isolated from reactions of MAlH4 (M=Li, Na, K) and different imines. Depending on the imine, double, triple or quadruple imine insertion has been observed. Prolonged reaction of LiAlH4 with PhC(H)=NtBu led to a side-reaction and gave the double insertion product LiAlH2[N]2 ([N]=N(tBu)CH2Ph) which at higher temperature reacts further by ortho-metallation of the Ph ring. A DFT study led to a number of conclusions. The most likely catalyst for hydrogenation of PhC(H)=NtBu with LiAlH4 is LiAlH2[N]2. Insertion of a third imine via a heterobimetallic transition state has a barrier of +23.2 kcal mol−1 (ΔH). The rate-determining step is hydrogenolysis of LiAlH[N]3 with H2 with a barrier of +29.2 kcal mol−1. In agreement with experiment, replacing Li for Na (or K) and Al for B (or Ga) led to higher calculated barriers. Also, the AlH4− anion showed very high barriers. Calculations support the experimentally observed effects of the imine substituents at C and N: the lowest barriers are calculated for imines with aryl-substituents at C and alkyl-substituents at N.
CRIS-Team Scopus Importer:2020-12-04
Keywords: DFT; heterobimetallic; hydride; hydrogenation; imine

Intramolecular Alkene Hydroamination with Hybrid Catalysts Consisting of a Metal Salt and a Neutral Organic Base - Stegner, Philipp; Fischer, Christian; Nguyen, D. Thao; Rösch, Andreas; Penafiel, Johanne; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2020)
Hybrid catalysts consisting of alkaline earth iodides (AeI2) and the Schwesinger base tBuP4 catalyse the intramolecular alkene hydroamination of H2C=CHCH2CR2CH2NH2 [CR2=CPh2, C(CH2)5, CMe2]. Activities decrease along the row: Ca > Sr >> Mg > Ba. Hybrid catalysts consisting of tBuP4 and ZnI2, AlI3, FeCI3 or NaI were found to be fully inactive. Also, the hybrid catalyst tBuP3/CaI2 was not active which means that the base strength of the non-nucleophilic organic base must be higher than that of tBuP3 (pKa BH+ = 38.6). Combinations of tBuP4 with CaX2 (X = Cl, Br, OiPr, OTf, NTf2) were found to be fully inactive which may in part be explained by poor solubility. The hybrid catalysis method is therefore limited to the combination tBuP4/CaI2 but the iodide ligands may be partially or fully replaced by chiral ligands. Chiral modifications of the hybrid catalysts gave in intramolecular alkene hydroamination ee values up to 33 %.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Calcium; Homogeneous catalysis; Intramolecular alkene hydroamination; Schwesinger bases

Lewis acidic alkaline earth metal complexes with a perfluorinated diphenylamide ligand - Fischer, Christian; Rösch, Andreas; Elsen, Holger; Ballmann, Gerd; Wiesinger, Michael; Langer, Jens; Färber, Christian; Harder, Sjoerd (Dalton Transactions, 2019)
Alkaline earth metal (Ae) chemistry with the anion [N(C 6 F 5 ) 2 ] - has been explored. Deprotonation of the amine (C 6 F 5 ) 2 NH, abbreviated in here as N F H, with 0.5 equivalent of AeN′′ 2 (N′′ = N(SiMe 3 ) 2 ) is fast and gave, dependent on the solvent, the complexes AeN F 2 , AeN F 2 ·(THF) 2 and AeN F 2 ·(Et 2 O) 2 (Ae = Mg, Ca, Sr). Using a 1/1 ratio, mixed amide complexes were obtained: N F AeN′′ (Ae = Mg, Ca, Sr). Crystal structures of the monomers AeN F 2 ·(THF) 2 (Ae = Mg, Ca, Sr) and AeN F 2 ·(Et 2 O) 2 (Ae = Mg, Ca) are presented and compared with those of AeN′′ 2 ·(THF) 2 . In addition, crystal structures of the homoleptic dimer (MgN F 2 ) 2 and the heteroleptic dimers (N F AeN′′) 2 (Ae = Mg, Ca, Sr) are discussed. All structures are strongly influenced by very short Ae⋯F contacts down to circa 2.11 Å (Mg), 2.50 Å (Ca) and 2.73 Å (Sr). AIM analysis illustrates that, although Ae⋯F contacts are short, there is no bond-critical-point along this axis, indicating an essentially electrostatic interaction. The monomeric complexes feature strong C 6 F 5 ⋯C 6 F 5 π-stacking, resulting in unusually acute N F -Ae-N F angles as small as 95°. Heteroleptic (N F AeN′′) 2 complexes retain their dimeric structure in C 6 D 6 solution and there is no indication of ligand scrambling by the Schlenk equilibrium, suggesting that an electron withdrawing ligand may stabilize heteroleptic complexes. According to DFT calculations, the heteroleptic arrangement is 70 kJ mol -1 more stable than the homoleptic dimers. The Lewis acidity of MgN F 2 has been quantified with the Gutmann-Beckett method and by calculation of the Fluoride-Ion-Affinity. The latter calculations show that the Lewis acidity of MgN F 2 and CaN F 2 is comparable to that of B(C 6 F 5 ) 3 . Dimeric (MgN F 2 ) 2 fully abstracts Et 3 PO from Et 3 PO·B(C 6 F 5 ) 3 and may have potential in Lewis acid catalysis.
CRIS-Team Scopus Importer:2019-06-04

Metallic Barium: A Versatile and Efficient Hydrogenation Catalyst - Stegner, Philipp; Färber, Christian; Zenneck, Ulrich; Knüpfer, Christian; Eyselein, Jonathan; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Ba metal was activated by evaporation and cocondensation with heptane. This black powder is a highly active hydrogenation catalyst for the reduction of a variety of unactivated (non-conjugated) mono-, di- and tri-substituted alkenes, tetraphenylethylene, benzene, a number of polycyclic aromatic hydrocarbons, aldimines, ketimines and various pyridines. The performance of metallic Ba in hydrogenation catalysis tops that of the hitherto most active molecular group 2 metal catalysts. Depending on the substrate, two different catalytic cycles are proposed. A: a classical metal hydride cycle and B: the Ba metal cycle. The latter is proposed for substrates that are easily reduced by Ba0, that is, conjugated alkenes, alkynes, annulated rings, imines and pyridines. In addition, a mechanism in which Ba0 and BaH2 are both essential is discussed. DFT calculations on benzene hydrogenation with a simple model system (Ba/BaH2) confirm that the presence of metallic Ba has an accelerating effect.
CRIS-Team Scopus Importer:2020-12-25
Keywords: alkaline earth metals; barium; hydride; hydrogenation catalysis; metal activation

Nucleophilic Aromatic Substitution at Benzene with Powerful Strontium Hydride and Alkyl Complexes - Rösch, Bastian; Gentner, Thomas; Elsen, Holger; Fischer, Christian; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
Key to the isolation of the first alkyl strontium complex was the synthesis of a strontium hydride complex that is stable towards ligand exchange reactions. This goal was achieved by using the super bulky beta-diketiminate ligand (BDI)-B-DIPeP (CH[C(Me)N-DIPeP](2), DIPeP = 2,6-diisopentylphenyl). Reaction of (BDI)-B-DIPeP-H with Sr[N(SiMe3)(2)](2) gave ((BDI)-B-DIPeP)SrN(SiMe3)(3) which was converted with PhSiH3 into [((BDI)-B-DIPeP)SrH2]. Dissolved in C6D6, the strontium hydride complex is stable up to 70 degrees C At 60 degrees C, H-D isotope exchange gave full conversion into ([(BDI)-B-DIPeP)SrD](2) and C6D5H. Since H-D exchange with D-2 is facile, the strontium hydride complex served as a catalyst for the deuteration of C6H6 by D-2. Reaction of [( (BDI)-B-DIPeP)SrH](2) with ethylene gave [( (BDI)-B-DIPeP)SrEt](2). The high reactivity of this alkyl strontium complex is demonstrated by facile ethylene polymerization and nucleophilic aromatic substitution with C6D6, giving alkylated aromatic products and [((BDI)-B-DIPeP)SrD](2).
CRIS-Team WoS Importer:2019-04-23

Selectivity control in the reactivity of dipyrromethene gallium(I) complexes - Richter, Tim; Thum, Stefan; Townrow, Oliver; Langer, Jens; Wiesinger, Michael; Harder, Sjoerd (Journal of Organometallic Chemistry, 2024)
Following the recent isolation and structural characterization of the first low-valent GaI complex with a monoanionic dipyrromethenide ligand (DPM), herein (DPM)GaI complexes with bulky aryl-substituents in the 1- and 9-positions are described. This study focusses on three DPM ligands with mesityl substituents (MesDPM), 2,6-diisopropylphenyl substituents (DIPPDPM), or 10-isopropyl-9-anthracenyl substituents (iPr-AnthDPM); the synthesis to the latter unknown ligand is described. The precursors (RDPM)GaI2 were obtained by reaction of the corresponding alkali metal complexes (RDPM)M (M = Na or K) with GaI3 and characterized by X-ray diffraction. Crystal structures show the efficient shielding of the GaI2 unit by two flanking aryl groups. In a subsequent reduction step, (DIPPDPM)GaI and (iPr-AnthDPM)GaI have been isolated. Comparison of the crystal structure of (DIPPDPM)GaI with that of a similar β-diketiminate GaI complex shows that the Ga center in the DPM complex is well shielded by flanking DIPP substituents. Despite this favorable ligand geometry, isolation of the corresponding (DPM)Ga=N(SiMe3) complexes failed due to further reaction with a second equivalent of Me3SiN3. This resulted in clean formation of the tetrazagallole complex (tBuDPM)Ga[N4(SiMe3)2] and the amide/azide combination (iPr-AnthDPM)Ga(N3)N(SiMe3)2, both structurally characterized by X-ray diffraction. Selective formation of both complexes shows that the substituents in the DPM ligand effectively control the course of the reaction. DFT calculations show that independent of the substituent (tBu, DIPP, or iPr-Anth) the amide/azide combination is always circa 20 kcal/mol more stable than the tetrazagallole product. The latter must therefore be formed by kinetic control.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Azide; Dipyrromethene ligand; Gallium; Imido; Low-valent

Stabilizing Magnesium Hydride Complexes with Neutral Ligands - Wiesinger, Michael; Maitland, Brant; Elsen, Holger; Pahl, Jürgen; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2019)
The reaction of Mg[N(SiMe3)(2)](2) with PhSiH3 in benzene at room temperature gave a white precipitate of approximate constitution MgH1.5N ''(0.5). This undefined hydride rich Mg salt can be dissolved by addition of well-known neutral donors, such as PMDTA, DABCO or the N-heterocyclic carbene I(Me)iPr (N,N '-diisopropyl-2,3-dimethylimidazol-2-ylidine). This allowed for crystallization and structural characterization of five new magnesium hydride complexes: Mg-2(mu-H)(2)N ''(2)center dot(PMDTA) (1), Mg-4(mu-H)(6)N ''(2)center dot(PMDTA)(2) (2), Mg-5(mu-H)(7)N ''(3)center dot(PMDTA)(2) (3), Mg-2(mu-H)(2)N ''(2)center dot(DABCO)(2) (4) and Mg-2(mu-H)(2)N ''(2)center dot(I(Me)iPr)(2) (5). The PMDTA complexes 1-3 were only isolated as mixtures that could not be separated but complexes 4 and 5 have been fully characterized. The structures of the Mg hydride complexes 1, 4 and 5 are reproduced well by DFT calculations (B3PW91/6-311++G**). Bonding between Mg and hydride is largely ionic (circa 80 %) and there is very little charge transfer from the neutral donor to Mg2+. The calculated solvation enthalpies (Delta H-solv) per ligand are -12.4 kcal/mol (PMDTA), -15.9 kcal/mol (DABCO) and -20.8 kcal/mol (I(Me)iPr). In complexes 4 and 5 Bond-Critical-Points are found between the two negatively charged hydride ligands. The very high electron densities of 0.15-0.16 e/angstrom(3) in these unusual BCP's are related to the short H-center dot center dot center dot H- distances of circa 2.55 angstrom.
CRIS-Team WoS Importer:2019-10-25

Synthesis, Structure, and Reactivity of a Superbulky low-Valent β-diketiminate Ga(I) Complex - Richter, Tim; Thum, Stefan; Townrow, Oliver; Wiesinger, Michael; Langer, Jens; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2024)
A low-valent GaI complex with the superbulky β-diketiminate ligand DIPePBDI (HC[C(Me)N−DIPeP]2, DIPeP=2,6-C(H)Et2-phenyl)) was obtained by reduction of (DIPePBDI)GaI2 (1) with KC8 in toluene. Considering that (BDI)GaI and analogue (BDI)AlI complexes are prone to decomposition and can generally only be obtained in low yields (20–40 %), the quantitative formation of (DIPePBDI)GaI (2) is remarkable and no doubt related to its excellent thermal stability even in refluxing toluene. Although the low-valent metal center in 2 is sterically protected by the superbulky DIPePBDI ligand, it is readily oxidized by N2O to give intermediate (DIPePBDI)Ga=O which readily decomposed by abstracting a proton from the backbone Me-substituent. Reaction with trimethylsilyl azide gave an intermediate imido complex (DIPePBDI)Ga=N(SiMe3)2 which reacted with a second equivalent of Me3SiN3 to a mixture of an azide/amido complex (DIPePBDI)GaN3[N(SiMe3)2] (4) and a tetrazagallole complex (DIPePBDI)Ga[N4(SiMe3)2] (5) in a 1 : 2 ratio. Whereas the azide/amido complex 4 could be structurally characterised, the tetraazagallole complex 5 was identified by NMR spectroscopy. DFT calculations on (DIPePBDI)GaI (2) and its reaction products complement this study.
CRIS-Team Scopus Importer:2024-06-07
Keywords: bulky; Gallium; Low-valent; β-diketiminate